[99ᵐTc]Tc-PSMA-I&S SPECT/CT quantitative parameters for risk stratification and metastasis prediction in primary prostate cancer: a retrospective study - Li, Ming; Gao, Zhenglian; Sun, Jiangming; Li, Xiangyu; Liang, Changping; He, Tao (Frontiers in Medicine, 2025)
BackgroundTo evaluate the diagnostic performance of [99ᵐTc]Tc-PSMA-I&S SPECT/CT in primary prostate cancer (PCa) detection and assess its ability to predict metastatic involvement and tumor aggressiveness in this single-center retrospective study.MethodsThis retrospective, single-center study enrolled 48 patients with suspected PCa (39 confirmed PCa, 9 benign conditions) who underwent [99ᵐTc]Tc-PSMA-I&S SPECT/CT between September 2022 and November 2023. Imaging was performed 4 h post-injection of 0.74 GBq [99ᵐTc]Tc-PSMA-I&S. Systematic prostate biopsy or surgical specimens served as the reference standard. Maximum standardized uptake values (SUVmax) were quantified in regions of enhanced prostatic uptake using Q.Volumetrix software. Correlations between SUVmax and clinicopathological parameters were analyzed using receiver operating characteristic (ROC) curves.Results[99ᵐTc]Tc-PSMA-I&S SPECT/CT achieved 100% sensitivity, 77.78% specificity, and 95.83% accuracy. SUVmax correlated significantly with Gleason score, PSA levels, risk stratification, and metastatic status. Median SUVmax was significantly elevated in patients with PSA > 20 ng/mL versus ≤20 ng/mL (13.20 vs. 6.68; p = 0.013) and Gleason score >7 versus ≤7 (13.60 vs. 6.75; p = 0.006). High-risk and metastatic cohorts demonstrated significantly higher SUVmax values (p = 0.010 and p = 0.023, respectively). For high-risk PCa prediction, optimal SUVmax cutoff was ≥10.85 (AUC = 0.84; sensitivity = 100%, specificity = 58%). For metastatic PCa detection, optimal cutoff was SUVmax ≥14.45 (AUC = 0.73; sensitivity = 92%, specificity = 50%).Conclusion[99ᵐTc]Tc-PSMA-I&S SPECT/CT demonstrates excellent diagnostic performance for PCa detection. SUVmax serves as a robust predictor for risk stratification and metastatic potential assessment.